Intuitive Mathematical Economics Series: Linear functions, their matrix form and the geometry of linear systems of equations - Sergio Pernice (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2019)
Matrices, their products, linear systems, and the underlying geometric ideas are presented in an intuitive and practical way for economics students and other students of the social sciences. Python Jupyter notebooks are used to present examples that enforce the geometric ideas.
Keywords: 330; Linear systems; Matrices